Expression of the miR-302/367 microRNA cluster is regulated by a conserved long non-coding host-gene - Karim Rahimi (Nature Portfolio, 2021)
Abstract MicroRNAs are important regulators of cellular functions. MiR-302/367 is a polycistronic miRNA cluster that can induce and maintain pluripotency. Here we investigate the transcriptional control and the processing of the miR-302 host-gene in mice. Our results indicate that the mmu-miR-302 host-gene is alternatively spliced, polyadenylated and exported from the nucleus. The regulatory sequences extend at least 2 kb upstream of the transcription start site and contain several conserved binding sites for both transcriptional activators and repressors. The gene structure and regulatory elements are highly conserved between mouse and human. So far, regulating miR-302 expression is the only known function of the miR-302 host-gene. Even though we here only provide one example, regulation of microRNA transcription might be a so far little recognized function of long non-coding RNA genes.